Geopolitic projection of Peru in the Antartic - Sueldo Mesones, Jaime Pio (2020)
At present, the Countries or States parties to the Treaty have incorporated a set of activities such as the installation of scientific research stations, bases located in important areas of maritime and air traffic, where Peru has had important participations. Therefore, the objective of this study is to analyze the development of the Geopolitics of Peru in Antarctica that satisfies the axes of national interest of Peru, mainly in the political-strategic, environmental-scientific and socio-economic factors. The type of research was theoretical-empirical where the design of the Grounded Theory was used as a research method, 4 expeditionary staff members and 6 members of the Peruvian Armed Forces were considered as population and the sample was theoretical; in addition, the observation guide, interview guide and records were used as instruments. Finally, it was concluded that, by establishing a new Scientific Station with the capacity to house contingents of scientists, scientific knowledge on global environmental problems affecting the National Territory will be made viable, linking it with other countries and building technical-scientific bridges. This will warrant that logistics for this purpose require greater budgetary funds, and that it meets the needs of transport by sea and air. But the singular that this is built in another area within the Antarctic peninsula, would strengthen our presence, both scientific and space interests.